Authentic Learning: The gift project - Bohemia, Erik; Davison, Gillian (Design and Technology Education: An International Journal, 2012)
Higher Education is experiencing an increasingly diverse student population. Students bring a range of skills and experiences to their courses; they have different backgrounds and different needs. This fluidity requires an approach to teaching that encompasses the social aspects of learning. It has been suggested that authentic approaches to teaching and learning can assist in offering a perspective on learning which views learning as ‘enabling participation in knowing’. We propose that the authentic learning practices developed in The Gift design project, discussed in this paper, constituted approaches which acknowledged that students’ interests and experience are intrinsically bound up with motivation and engagement and, as such, have a major influence on the ways in which learning is constituted and developed. The Gift project has developed a range of innovative formative strategies which have provided both students and tutors with opportunities to become involved in peer assessment and review, peer feedback and reflection on learning outcomes. This re-conceptualisation of the assessment process has provided valuable insights into the development of learning skills such as problem solving, critical analysis, and the development of creativity and learner autonomy.